Accountability of Donation Receipts in Child Social Welfare Institutions: Akuntabilitas Penerimaan Donasi Di Lembaga Kesejahteraan Sosial Anak (LKSA) Robbani Singosari Malang - Arum Kusuma Dewi; Syamsul Bahri; Endah Puspitosarie (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Donation-based non-profit organizations require a robust accountability system to maintain public trust and maintain the institution's sustainability. The Child Welfare Institution (LKSA) relies heavily on public donations to fund childcare, education, and development programs. Following the COVID-19 pandemic, the uncertainty of government assistance has increased reliance on individual donors, making accountability for donation receipts and management even more crucial. This study aims to analyze the implementation of accountability for donation receipts and management at LKSA Robbani Singosari, Malang Regency. The study used a qualitative descriptive approach, collecting data through in-depth interviews, observations, and documentation studies of financial records and activity reports. The results indicate that LKSA Robbani has implemented routine recording of donation receipts, e-receipt issuance, internal financial documentation, and publication of activity reports through social media. However, limitations remain in the preparation of structured and standardized periodic financial reports. Strengthening the reporting system and improving transparency mechanisms are recommended to increase donor trust and the institution's sustainability. This study contributes to the development of accountability practices in donation-based social institutions.